Looking at Payments for Ecosystems Services in the Philippines - Sonny N. Domingo; Arvie Joy A. Manejar; John Joseph S. Ocbina (Philippine Institute for Development Studies (PIDS), 2022)
The payment for ecosystem services (PES) emerges as part of an arsenal of tools for innovative domestic financing for otherwise absent markets relating to natural resource management. Its traditional framework aspects of conditionality, voluntary transaction, at least one buyer and seller, and an identified ecosystem service. However, most domestic cases in the Philippines do not meet the first two criteria. Further to this, existing templates remain dispersed and not harmonized. Common barriers that contribute to these are negotiation bottlenecks, missing policies, and institutions, weak sustainability measures, and data unavailability. Stronger integration with sector-specific initiatives involves pursuing in the long run a legal platform for PES at NGA and subnational levels alongside natural capital management, framing sustainable mechanisms, capitalizing on evolving definition, and riding on ongoing efforts at the national level.
Keywords: 330; payments for ecosystem services; environment; ecological integrity; ecosystem services